Monosyllabic and polysyllabic words used in Togay Murod's "The Night of the Neighing Horse" (Eurasian Journal of Research, Development and Innovation, 2025)
This article describes the use of single-meaning and multi-meaning words in the language of Togay Murod's story, and the writer's skill in using these tools to reveal the essence of the work.